Study On The Addition Of Taro, Mung Bean, Wheat Flours On The Quality Of Cookies - Wita Dola Rista Sidabutar; Rona Joharmi Nainggolan; Ridwansyah Ridwansyah (Universitas Sumatera Utara, 2013)
The research was aimed to investigate the effect of addition of taro and mung bean flours on the quality of cookies. The reseach had been performed using factorial completely randomized design, with one factor i.e : taro flour, mung bean flour and wheat flour (T): 70%:0%:30%, 60%:10%:30%, 50%:20%:30%, 40%:30%:30%, 30%:40%:30%, 20%:50%:30%, 10%:60%:30%, 0%:70%:30%. Parameters analyzed were water content, ash content, fat content, protein content, fiber content, cookies crispy test with instrometer and organoleptic values (flavor, taste and texture).The result showed that the ratio of taro flour, mung bean flour and wheat flour had significant effect on all parameters.The 70%:0%:30% composition produced the best cookies in organoleptic values. . Key words : Taro flour, mung bean flour, wheat flour,cookies